Organogénesis y ciclos estacionales del órgano de Bidder en las larvas y los juveniles de Bufo arenarum (Anura: bufonidae) - Echeverría, Dinorah Diana (1990)
The Bidder's organ (BO) differentiation takes place at stage 25 (stages; Echeverría et al., 1981). Oogonia and young oocytes (a and b) are placed at BO periphery. During the larval period the BO grows faster than the pregonad (=previous gonad), until the metamorphosis period occurs. On young toads (from one to three years) and on adult male toads (fourth year) the BO shows celular seasonal cycles. The celular cycles shows to steps: a) partial oogenesis in the peripherical surface with prolific and development celular process (proliferation and growth) of the oogonias and small oocytes. b) Development of the oocytes inside the organ: development up to their hypertrophy that finish in degeneration of the oldest oocytes. After that, the empty and atresic folicles take place. There is a comparision between the male and female BO development in young toads